ANXIETY OF ENGLISH LEARNING AND LEARNING STRATEGIES’ INFLUENCE TO SPEAKING ABILITY - Yuni Utami Asih (IAIN MADURA, 2012)
This study focuses on investigating the influence of anxiety in learning English, learning strategies and English speaking ability of the students where English is their foreign language. Results of the study show that most of the respondents (82.01% = 110 respondents) belong to the second level of foreign language classroom anxiety or medium anxiety. Meanwhile, language learning strategies are applied in varied ways and there is no single strategy dominates the students’ choice. Speaking ability test shows the scores of the students range from 53 to 82 where only half number of the students achieves satisfying scores (70-82). Based on the statistical calculation using multiple regression, the value of correlation between anxiety level and speaking ability is -0.325. Therefore, the statistical hypothesis that stating anxiety of the learning of English gives significant influence to speaking ability is accepted (Ho is rejected and Ha is accepted). On the contrary, for the correlation between learning strategies and speaking ability the value is 0.104 with significant level is 0.116. The significant level is higher than 0.05 displays that there is no correlation between those two variables. Result of ANOVA is F = 8.213, sig. = 0.00 (less than 0.05). The multiple regression model of the result of this study is Ŷ = 90.057 - 0.159X1 - 0.031X2. This model indicates that the regression is significant. The result also shows that anxiety level and learning strategies give low influence to speaking ability (11.1%).